The U-Shaped Effect and Its Reversal Mechanism of Export and Innovation—Evidence From Chinese Industrial Enterprises - Cao, Xin; Li, Peng; Fan, Limin; Jiang, Yuan; Huang, Xiaozhi (Frontiers in Ecology and Evolution, 2022)
Chinese firms are advancing their internationalization process at a surprisingly rapid pace, which is at odds with the descriptions of mainstream theories of corporate internationalization, such as the internalization theory and the eclectic theory of international production. In this context, a large number of existing literatures have examined the learning-by-export effect but have not agreed on its advantages. In the framework of recombinatory view of innovation, we integrate the resource-based view and the institution-based view, taking Chinese industrial enterprises as the research object, taking the export intensity and the output value of new products as the main indicators. We using the fixed effect model based on the Chinese Industrial Enterprise Database construction with China's Marketization Index.Then this study aims to examine the relationship between exports and innovation. Research results show a nonlinear effect, that is U-shaped relationship between exports and innovation; furthermore, the relationships are influenced by institutional factors at the provincial level. The institutional development level is a reverse mechanism of relationship between exports and innovation; when the institutional development level is higher, the relationship between exports and innovation has an inverted U shape. The findings enhance the understanding of export innovation from the perspective of resources and institutions, and export enterprise innovation management can benefit from its significant insights.